A unidirectional quantum cascade ring laser - Nshii, C.; Ironside, Charlie; Sorel, M.; Slight, T.; Zhang, S.; Revin, D.; Cockburn, J. (American Institute of Physics, 2010)
We report on the design, fabrication, and characterization of a unidirectional quantum cascade ring laser operating at a wavelength of around 3.4 µm at 200 K. A unidirectional operation is achieved by incorporating an "S-shaped" crossover waveguide in a manner that it couples light from the counterclockwise direction to the preferred clockwise direction. The ring laser unidirectionality is confirmed by measuring the counterpropagating wave suppression ratio (CWSR) as a function of injection current. At 1.5 times the threshold current, the CWSR is 9 that is 90% of the light is emitted in the favored (clockwise) direction. © 2010 American Institute of Physics.